Glosa do wyroku Naczelnego Sądu Administracyjnego z 9 grudnia 2022 r., sygn. akt I OSK 555/201 : niedopuszczalność ponownej oceny stanu faktycznego w postępowaniu nieważnościowym oraz konwalidowania zachowania dłużnika alimentacyjnego w sprawie uznania go za uchylającego się od zobowiązań alimentacyjnych - Kosicki, Tomasz (Studia Prawa Publicznego, 2023)
The gloss is devoted to the problem of the admissibility of validating the maintenance debtor’s behavior in the proceedings to recognize him as evading maintenance obligations in the light of the provisions of the Act of 7 September 2007 on assistance to persons entitled to maintenance. It also deals with the essence of the proceedings regarding the annulment of the decision. Although the court of first instance did not allow such a possibility, the analysis carried out in the paper shows that there are legal grounds for this. The paper concludes that if, after the explanatory proceedings are completed, but before the decision is issued, the maintenance debtor reconsiders and consents to a maintenance interview with him and for a declaration of assets to be taken from him, the public administration body should take these circumstances into account when making a decision. There was criticism of the thesis that allowing for the validation of behavior contradicts the purpose of the introduced solutions aimed at mobilizing debtors to fulfill their obligations towards those entitled to maintenance. It is pointed out that such an approach from the authorities may have further undesirable consequences, as the effect of issuing a decision on the above-mentioned subject is to initiate separate proceedings regarding the suspension of a driving license. The study also analyzes the way in which the premises for initiating the above proceedings are understood, proposing a different understanding of them. It was concluded that the positive and negative premises for initiating proceedings should be understood by the authority in a functional manner. The position of the Supreme Administrative Court was deemed correct, namely that in nullity proceedings the assessment made by the authority concerns only the examination of whether the decision being contested is affected by one of the defects specified in the Code of Administrative Procedure.